Antiviral activity of Scutellaria baicalensis Georgi Extract against Getah virus in vivo and in vitro - Liu, Baoling; Wang, Yuling; Shao, Lina; Chen, Yuanhang; Xu, Zhiwen; Zhu, Ling (Frontiers in Veterinary Science, 2025)
IntroductionThe Getah virus (GETV) is a zoonotic arbovirus causing disease in humans and animals, a member of the Alphavirus genus. Currently, approved antiviral drugs and vaccines against alphaviruses are few available. This study aimed to investigate the anti-GETV activity of the Extract of Scutellaria baicalensis Georgi (ESG) in vivo and in vitro.MethodsThe cytotoxic effects of ESG on BHK-21 cells were quantitatively evaluated through the MTT assay. Quantitative analysis of viral replication was performed using qRT-PCR, while E2 protein expression was analyzed through western blotting. Furthermore, molecular docking simulations were conducted to examine the binding affinity between the principal bioactive constituents of ESG and the E2 structural proteins. Additionally, the therapeutic potential of ESG in alleviating viremia was evaluated in GETV-infected mouse models.ResultsThe results showed that ESG significantly attenuated the cytopathic effects induced by GETV infection in BHK-21 cells, concurrently reducing both viral replication and E2 protein expression. Notably, ESG exhibited its most potent antiviral activity during the viral attachment and entry phases, with IC50 values of 3.69 μg/mL and 3.94 μg/mL, respectively. At a concentration of 10 μg/mL, ESG achieved 95.08% inhibition efficiency against viral attachment. Furthermore, in vivo studies revealed that ESG treatment significantly reduced the peak viral load and shortened the duration of viremia in GETV-infected mice. The main components of ESG are baicalin and baicalein, and molecular docking simulations demonstrated strong binding affinities between these compounds and the active site of GETV E2 protein, with docking scores of −6.99 kcal/mol for baicalin and −5.21 kcal/mol for baicalein.ConclusionThe experimental findings demonstrate that ESG exhibits significant antiviral efficacy against GETV infection both in vitro and in vivo. These results indicate that ESG represents a promising therapeutic candidate for the prevention and treatment of GETV infections. Mechanistically, the antiviral activity of ESG appears to be mediated, at least in part, through the modulation of E2 protein expression.